Argumentasi Penuntut Umum Mengajukan Kasasi Terhadap Putusan Bebas Pengadilan Negeri Yogyakarta Dalam Tindak Pidana Perbuatan Merugikan Pemiutang - Amalia Faturrahmah Adiwana (Verstek, 2017)
This study aims to determine whether the reason for cassation by the prosecutor in the case of acts detrimental creditor has been in accordance with the provisions of Article 253 the Code of Criminal Procedure and whether the consideration of the judges of the Supreme Court in deciding the appeal inaccordance with the provisions of Article 256 in conjunction with Article 193 paragraph (1) The Book of the Law of Criminal Procedure.       This study is a normative legal perskriptif, using a case approach. Based on the results of this study concluded that the public prosecutor's arguments in accordance with article 253 Criminal Procedure Code and the consideration of the judges of the Supreme Court in deciding the case in accordance with the provisions of Article 256 in conjunction with Article 193 of the Criminal Procedure Code.       Keywords: Remedy of Cassation, acts detrimental creditor, Supreme Courtdecisions.